Imagens simbólicas e metáforas em Fazendeiro do ar , de Carlos Drummond de Andrade - Bruzzi, Maria Lúcia Casasanta (2011)
This essay presents in its first chapter the concepts of images and symbols. In the second chapter, it deals with Gaston Bachelard s theories applied to examples from the poems of Fazendeiro do Ar, written by Carlos Drummond de Andrade. The metaphors are studied in the third chapter. They are based in Susanne Langer s theories and are also applied to examples from the poems of the same masterpiece. In its fourth chapter the conclusion is a deeper study of images, symbols and metaphors of two poems, namely Estrada and Elegia .